Intimate relationships and social change : the dynamic nature of dating, mating, and coupling - Scott, Christina L.; Blair, Sampson Lee (Bingley, U.K. : Emerald Publishing Limited, 2017)
Over the past few decades, there has been a dynamic world-wide societal shift away from traditional routes for finding a partner and establishing intimate relationships. This multidisciplinary volume investigates the impact of online dating and the role of technology in relationship formation; the nature of cohabitation and its relative meaning with marriage; assortative mating patterns; the role of parents and siblings in the selection of a partner; gender and sexuality within dating and mating; evolving forms of non-traditional marriage; the interplay of personality and sociodemographic traits within partner selection; and the role of race, ethnicity, and religion in dating and mating. Together, this collection provides a unique and truly global collection of research on the nature of dating, mating, and coupling, as they occur across a variety of cultures.
Prelims -- Enjoy the heat of a log, and heed the advice of the elders: religious, educational, and neighborhood determinants of parental influence on spousal choice in Nepal -- ...And here we are..: influencing factors of intimate partner preference among married couples in Nigeria -- Intergenerational conflicts and resistance of daughters in suburban Turkey -- Changing gender role expectations in the family formation process through the lens of ambivalence -- Educational assortative mating and female breadwinning trajectories: a group-based trajectory analysis -- Dating & mating in adolescence: a model to predict pathways of relationship outcomes -- The transition to adulthood in individualistic and collectivistic cultures: prevalence and timing of premarital cohabitation and first marriage in Germany and China -- Marriage and cohabitation among rural and urban women in western Mexico -- Living apart together relationships in later life: constructing an account of relational maintenance -- Technology use and its association with romantic relationships -- The aftermath of dating relationship dissolution in emerging adulthood: a review -- About the Authors -- Index.
Includes index.
Includes bibliographical references.
Print version record
Keywords: Dating, relationships, living together & marriage; Dating (Social customs); Mate selection; Marriage